Simultaneous analysis of the enantiomers of verapamil and norverapamil in rat plasma by liquid chromatography tandem mass spectrometry - Mateus, Fabiano Henrique; Lepera, José Salvador [UNESP]; Marques, Maria Paula; Boralli, Vanessa Bergamin; Lanchote, Vera Lucia (Elsevier B.V., 2007)
An enantioselective micromethod for the simultaneous analysis of verapamil (VER) and norverapamil (NOR) in plasma was developed, validated and applied to the study of the kinetic disposition of VER and NOR after the administration of a single oral dose of racemic-VER to rats. VER, NOR and the internal standard (paroxetine) were extracted from only 100-mu L plasma samples using n-hexane and the enantiomers were resolved on a Chiralpak AD column using n-hexane:isopropanol: ethanol: diethyl ami ne (88:6:6:0.1) as the mobile phase. The analyses were performed in the selected reaction monitoring mode. Transitions 456 > 166 for VER enantiomers, 441 > 166 for NOR enantiomers and 330 > 193 for the internal standard were monitored and the method had a total chromatographic run time of 12 min. The method allows the determination of VER and NOR enantiomers at plasma levels as low as 1.0 ng/mL. Racemic VER hydrochloride (10 mg/kg) was given to male Wistar rats by gavage and blood samples were collected from 0 to 6.0 h(n = 6 at each time point). The concentration of (-)-(S)-VER was three folds higher than (+)-(R)-VER, with an AUC ratio (-)/(+) of 2.66. Oral clearance values were 12.17 and 28.77 L/h/kg for (-)-(S)-VER and (+)-(R)-VER, respectively. The pharmacokinetic parameters of NOR were not shown to be enantioselective. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: verapamil; enantiomers; metabolism; rats; LC-MS/MS